A fatal case of acute Marchiafava-Bignami disease complicated by acute abdomen– a case report - Bence Prohászka; Novák Pál Kaposi; Zsuzsanna Jánosi; Bence Gunda; Ildikó Pákozdy; Szabolcs Gaál-Marschal; Dóra Melicher; Bánk G. Fenyves; Csaba Varga (International Journal of Emergency Medicine)
Abstract Background Marchiafava-Bignami Disease (MBD) is a rare disorder characterized by demyelination and necrosis of the corpus callosum, with only 300 documented cases worldwide. Chronic alcohol consumption and vitamin B-complex deficiencies are contributing factors. Acute cases may present with a range of neurological symptoms, including seizures and coma. Subacute and chronic forms can lead to interhemispheric disconnection syndrome and progressive dementia. Case presentation We present the case of a young male patient’s first hospital admission due to an acute decline in conscious level. A detailed history revealed regular alcohol consumption and substandard living conditions. The deterioration in consciousness was attributed to the diagnosis of MBD based on neurological signs, characteristic brain imaging findings, and a history of alcohol use. In addition, a small bowel perforation was also diagnosed. Supportive therapy and thiamine were initiated, and the patient was transferred to surgery for an operation. After two surgeries, the perforation was covered. The patient’s level of consciousness showed slight improvement; however, the psychiatrist noted severe cognitive deficits. Ultimately, the patient entered a septic state and passed away. Conclusion Acute MBD can potentially cause altered mental state, coma, and death; however, cases can be complicated by other emergency conditions. This case demonstrates the importance of a multidisciplinary approach.